Potential therapeutic targets of Aquilaria malaccensis leaf extract: A network pharmacology approach - Hashim, Yumi Zuhanis Has-Yun; Eissa, Manar; Abbas, Phirdaous; Samsudin, Nurhusna; Abd Warif, Nor Malia (Malaysian Society for Molecular Biology and Biotechnology (MSMBB), 2025)
Agarwood has been extensively studied for its potential as an anti-inflammatory and anti-cancer agent. However, there is no consensus on the mechanisms of action due to variations in empirical settings. Network pharmacology, which integrates big data and artificial intelligence, offers a systematic means to elucidate compound–gene–pathway interactions. This study employed network pharmacology to catalogue the molecular interactions of Aquilaria malaccensis aqueous leaf extract with an emphasis on anti-inflammatory and immunomodulatory activities. A total of 78 bioactive compounds were identified, of which seven key compounds—mangiferin, genkwanin, aquisiflavoside, luteolin, 3’-hydroxygenkwanin, sakuranetin, and velutin—were highlighted as potential modulators of inflammatory responses. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed 158 related pathways, with 138 significantly enriched. Among the top-ranked pathways, the atherosclerosis pathway and proteoglycans in cancer pathway were notably associated with inflammation and tumour progression. Furthermore, eight overlapping genes (AKT1, CCND1, CXCL12, EGFR, MMP9, NFKB1, TGFB1, TNF) were identified as potential therapeutic targets. Collectively, these findings illustrate how A. malaccensis compounds may modulate the molecular cross-talk between inflammation and cancer, providing a foundation for the development of nature-based therapies for inflammatory disorders and cancer.